FTAs the Chinese Way: The Chile-China and Peru-China Free Trade Agreements - Wise, Carol (Universidad del Pacífico, 2012)
Chinese-style FTAs in South America have proved to be unique in three respects: first, due to China’s continued classification as a non-market developing economy at the World Trade Organization (WTO), the Chile-China and Peru-China FTAs technically classify as South-South deals. Yet, the nature of exchange between China and these two South American countries is based on a traditional pattern of comparative advantage more akin to North-Southtrade relations at the turn of the 20th century whereby these South American countries export primary goods to China and import manufactures back. In contrast, today’s North-South deals are oriented more toward market access for manufactured goods and the implementation of new rules in the realm of services, investment, and intellectual property. Second, it was this more traditional pattern of exchange, and China’s thirst for the mineral commodities that Chile and Peru hold in abundance, that dictated the terms of both ofthese FTAs from the Chinese angle. Third, in order to secure the supply of these commodities China readily conceded to numerous market access restrictions within both FTAs. This analysis suggests that both Chile and Peru entered these negotiations in search of greater non-mining foreign direct investment (FDI) from China and to increase non-traditional exports to the Chinese market. However, China has thus far shown little interest outside of the mining sector in both countries. In light of these three points, these FTAs with China defy standing explanations for why developing countries would commit to the implementation of a bilateral FTA with a major economic power.